Chloroquine treatment of severe malaria in children. Pharmacokinetics, toxicity, and new dosage recommendations. - White, N; Miller, K; Churchill, F; Berry, C; Brown, J; Williams, S; Greenwood, B (1988)
Although empirical regimens of parenteral chloroquine have been used extensively to treat severe malaria for 40 years, recent recommendations state that parenteral chloroquine should no longer be used because of potential toxicity. We studied prospectively the pharmacokinetics and toxicity of seven chloroquine regimens in 58 Gambian children with severe chloroquine-sensitive falciparum malaria. In all regimens the total cumulative dose was 25 mg of chloroquine base per kilogram of body weight. Chloroquine was rapidly absorbed after either intramuscular or subcutaneous administration (5 mg of base per kilogram every 12 hours), producing high peak blood concentrations but transient hypotension in 5 of 18 patients (28 percent). Intermittent intravenous infusion (5 mg of base per kilogram over 4 hours, repeated every 12 hours) also produced wide fluctuations in chloroquine levels, suggesting incomplete distribution from a small central compartment. Continuous infusion (0.83 mg of base per kilogram per hour for 30 hours) and smaller, more frequent intramuscular or subcutaneous injections of chloroquine (3.5 mg of base per kilogram every 6 hours) produced smoother blood-concentration profiles with lower early peak levels and no adverse cardiovascular or neurologic effects. Chloroquine given by nasogastric tube (initial dose, 10 mg of base per kilogram) was absorbed well, even in comatose children. We conclude that simple alterations in dosage and frequency of administration can give parenteral chloroquine an acceptable therapeutic ratio and reinstate it as the treatment of choice for severe malaria in areas where chloroquine resistance is not a major problem.